Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
On January 19, 2024, the FDA granted traditional approval to erdafitinib for patients with locally advanced or metastatic urothelial carcinoma (la/mUC) with susceptible FGFR3 genetic alterations, as determined by an FDA-approved companion diagnostic test, whose disease has progressed on or after at least one line of prior systemic therapy. Substantial evidence of effectiveness was obtained from BLC3001 (THOR, NCT03390504) Cohort 1, which was an open-label trial in which 266 patients with FGFR3-altered la/mUC were randomized 1:1 to receive erdafitinib (8 mg once daily with potential up-titration to 9 mg) versus chemotherapy (docetaxel 75 mg/m2 every 3 weeks or vinflunine 320 mg/m2 every 3 weeks) until disease progression or unacceptable toxicity. The primary endpoint was overall survival (OS). Statistically significant improvements in OS, progression-free survival, and objective response rate were demonstrated for erdafitinib compared with chemotherapy. Median OS was 12.1 months (95% CI: 10.3, 16.4) in the erdafitinib arm and 7.8 months (95% CI: 6.5, 11.1) in the chemotherapy arm (HR: 0.64, 95% CI: 0.47, 0.88; p=0.0050). Based on BLC3001 Cohort 2 results showing no OS benefit of erdafitinib versus pembrolizumab (HR 1.18, 95% CI: 0.92, 1.51), the approval includes a limitation of use: erdafitinib is not recommended for the treatment of patients who are eligible for and have not received prior PD-(L)1 inhibitor therapy. This article summarizes the data and the FDA thought process supporting traditional approval of erdafitinib, including the rationale for not requiring specific types of prior systemic therapy in the indication statement.